Climatic Conditions of Vietnam and Potential of Non-Conventional Energy Sources - B. M. Khroustalev; Tuan Kiet Ngo; Thuy Nga Nguyen (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains an approximate evaluation of solar and wind energy potential in Vietnam. Possible energy generation using non-conventional energy sources is cited for a number of regions in Vietnam.